Prototyping and low-volume production - Thompson, Rob, ....- (New York : Thames & Hudson, 2011)
Designers are presented with a myriad of choices when preparing work for manufacture. Whether professionals or students, they must be thoroughly knowledgeable about how their designs can be produced efficiently and effectively. Here is one the first books in a new series built on the authority of Rob Thompson "s highly acclaimed Manufacturing Processes for Design Professionals. Clearly presented and highly detailed, each book is organized into three easily referenced parts: forming, joining, and finishing. An explanation of each manufacturing process provides a full technical description; analysis of typical applications; and information on cost, speed, and environmental impact. Step-by-step case studies show a product or component being manufactured by a leading international supplier. Photographs of geometry, detail, color, and surface finish complete the practical information.
This book features new content selected specifically for the needs of students who create prototypes, designs for low-volume production runs, and designs that utilize craft. With some 450 specially commissioned photographs and technical illustrations, it describes more than 30 manufacturing processes, from the traditional and established to emerging technologies--
Includes bibliographical references (p. 189-190) and index.
Keywords: Industrial engineering; Industrieel ontwerpen; Manufacturing processes; Production management; Prototypes, Engineering -- Design